1999
DOI: 10.3141/1654-08
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Density Readings and Core Densities: A Comparative Study

Abstract: Presented are the findings of an investigation performed to identify possible correlations between nuclear density gauge readings and core density results. The nuclear density data were collected on a Superpave section of I-95 in Brevard County, Florida. Core samples also were obtained from this section for laboratory density determination. Five gauge units [Troxler models 3401, 3440 (two units), 3450, and 4640] and three core density methods (Florida test method FM 1-T 166, ASTM D1188, and dimensional analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…In traditional HMA paving, the measurement of mat density is one of the primary methods of quality control. The most common quality control-quality assurance techniques for mat density are (a) coring and directly measuring the bulk density and (b) nondestructive density gauge testing (3). Unfortunately, these methods have severe limitations when considered for use on thin HMA overlays.…”
mentioning
confidence: 99%
“…In traditional HMA paving, the measurement of mat density is one of the primary methods of quality control. The most common quality control-quality assurance techniques for mat density are (a) coring and directly measuring the bulk density and (b) nondestructive density gauge testing (3). Unfortunately, these methods have severe limitations when considered for use on thin HMA overlays.…”
mentioning
confidence: 99%
“…Although a nuclear gauge could provide an accurate measurement, based on an inaccurate calibration table, it would be impossible to obtain a correct result. Therefore, it is not surprising to see a poor correlation of the density test results by the nuclear method and other test methods (Alexander and Doty, 1984;Jameson, 1985aJameson, , 1985bBurati and Elzoghbi, 1987;Sander et al, 1994;Choubane et al, 1999;and Padlo et al 2005). Using the new density calibration method, it is expected that the correlation between nuclear method and other test method will be improved.…”
Section: Demonstrations Of the New Calibration Methodsmentioning
confidence: 99%
“…Jameson (1985aJameson ( , 1985b compared the test results of the nuclear gauge, the sand replacement method, and the in-place coarse aggregate density method in a crashed rock pavement. Alexander and Doty (1984), Burati andElzoghbi (1987), Sander et al (1994), Choubane et al (1999), andPadlo et al (2005) respectively studied the correlation of nuclear density results and core densities for asphalt pavements. All of these research results showed that considerable differences exist between the nuclear test method and other test methods.…”
Section: Introductionmentioning
confidence: 99%
“…Cores can be taken only after the compacted bituminous mixture has cooled sufficiently, and the cored samples need to be completely dry before bulk density measurements can be performed in the field or laboratory. Because of the destructive nature of extracting cores, contractors and agencies have implemented for many years both non‐destructive nuclear and non‐nuclear density gauges for quality control and in some cases acceptance (Smith and Diefenderfer ; Choubane et al ). Non‐destructive gauges allow for a more rapid assessment of the in situ density during construction.…”
Section: Introductionmentioning
confidence: 99%